The continuous measurement of the potential during the process of the electrochemical copper setting - Białostocka, Anna Maria; Walendziuk, Wojciech (Видавництво Львівської політехніки, 2011)
In the article will be presented usefulness of the computer modeling support through the remote measurements in the electrochemical technologies. Modeling of the electrolytic covers demand of problems solution connection with current distribution in the electrolyte, electrodes shape and composition of the electrochemical environmental in which the process takes place. Adapted methodology is used to potential analyze and its influence on the covered layer structure and Its topology. Classification of methods properties makes possibility of its valuation in the case of elasticity, usefulness in the galvanic process and conforming in practice. W artykule przedstawiona zostanie przydatność komputerowego wspomagania modelowania poprzez przeprowadzanie zdalnych pomiarów w technologiach elektrochemicznych. Modelowanie powłok elektrolitycznych wymaga rozwiązania problemów związanych między innymi z rozkładem prądu w elektrolicie, kształtem elektrod i składem elektrochemicznym środowiska, w którym zachodzi proces. Zastosowaną rnetodologię wykorzystuje się do analizy potencjałui jego późniejszego wpływu na strukturę osadzonej powłoki i jej topologię. Klasyfikacja własności tej metody umożliwi jej ocenę pod względem elastyczności i przydatności w procesie galwanizacji oraz możliwość późniejszego zastosowania w praktyce.
Keywords: electrocrystallization; electrode processes; copper surface layer; additive electrodes; elektrokrystalizacja; procesy elektrodowe; powierzchniowa warstwa miedzi; elektrody dodatkowe